ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT KESEJAHTERAAN LANSIA DI KECAMATAN MARGA KABUPATEN TABANAN - Pratiwi, Ida Ayu Ratih; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Elderly is an aging process with increasing age of the individual. The life of the elderly is often perceived negatively, or does not provide much benefit to the family and society. Therefore, a study is needed to support the welfare of the elderly in Marga District, Tabanan Regency. This study aims to analyze the influence of health factors, level of religiosity, economic conditions, and family support simultaneously and partially on the welfare of the elderly. This research was conducted by taking samples from 3 villages namely Kukuh Village, Payangan Village and Geluntung Village. The sampling method used was non-probability sampling, which was determined using a purposive technique combined with snowball sampling with a total sample of 96 elderly residents. The data analysis technique used is multiple linear regression analysis. Based on the results of the study, it can be concluded that health factors, level of religiosity, economic conditions, and family support simultaneously have a significant effect on the welfare of the elderly in Marga District, Tabanan Regency. Health factors, level of religiosity, economic conditions, and family support partially have a positive and significant effect on the welfare. The author suggests that there is a need for a role for the family to better maintain and establish good interactions, and the family must also pay more attention to the basic needs of the elderly, provide support to the elderly both in terms of mental support, moral support, economic support, and so on. Keywords : health factors, level of religiosity, economic conditions, and family support